The affordances of informant design in educational game development. (1st January 2013) - Kim, Beaumie; Tan, Lynde; Kim, Mi Song
This paper argues that in 'educational' game development, there is often a gap between design and learning. It suggests how involving learners in the design process, known as the informant design approach, is able to close this gap. One key affordance of such an approach is the provision of learning opportunities for the learners themselves where designing and learning are intertwined. Specifically, learners had opportunities to use their experiences as their resources for learning and game design. They were capable of drawing on their knowledge of their lifeworlds, particularly adolescents' gaming culture and Earth phenomena, when suggesting game ideas for learning.